Politics and Law - Liu, Tianmiao (Understanding Chinese culture, 2018)
Chapter 2, “Politics and Law,” was originally written by Liu Tianmiao, and translated by Wu Wenquan for the present book. Arranged chronologically, the chapter first traces the evolution of political systems and focuses on characteristic political practices in each period of Chinese history. It then looks at the legal system’s historical development and introduces typical legal practices and various legal codes.